La Arquitectura más allá del plano físico; relación existente entre el ámbito de la Arquitectura y el Videojuego (2022)
It is proposed in the following research to establish how architectural criteria of architectural coherence, aesthetics, and meaning are necessary in the development or creation of virtual scenarios to achieve, to a lesser or greater extent, create or enhance the immersion sensations to these worlds for the users who make use of these projects. For the correct development of this thesis of degree it is necessary to know movements, thoughts, references on the inspiring bases of the virtual worlds or video games, this in order to build an elementary family tree that will bring us closer to understanding where the main ideas that gave rise to these projects and how these ideas that transcended in the real world, can influence the virtual worlds.